A novel opto-mechanical system constituted by LEDs to employment in photobiostimulation: Clinical application in optical therapy. Issue 1 (2012) - Barbosa, Celso J.; Teles, Crisaldo; Moreira, Leonardo M.; Damião, Álvaro J.; de Lima, Carlos J.
Abstract : Optical techniques of photobiostimulation, which use transducer as lasers and LEDs, have been employed in the treatment of several diseases. The laser systems usually irradiate in a reduced area of the target biological tissue, presenting high cost of acquisition. Devices with a LED of Surface Mount Device (SMD) type have high angle of light emission, implying in intense decrease of the density of optical potency. Furthermore, the use of this device requires the utilization of a cooling system, which provokes an increase in the cost of this product. In the present work, it is suggested the application of a novel opto-mechanical device constituted by usual LEDs with package dimension of 5 mm of diameter, which presents significant efficient and very low cost. The arrangement of the geometric configuration of these LEDs is elaborated in such way that all units emit photons in a unique section of an specific area. An opto-mechanical system was developed, which includes seven LEDs, being that six of these LEDs are disposed in a specific angle around a unique central LED. It is important to notice that all the opto-mechanical system with seven LEDs emit light in a unique area. Besides, a methodology was employed to allow the verification of the distribution of light intensity upon this respective area. This arrangement allows that this novel device propitiate measurements of the degree of homogeneity of the light intensity in specific areas, which are accessed by the seven light emitting units. The potency employing LEDs in the red (visible) and near infrared regions were also measured, being that the result demonstrated the capability of clinical application in optical therapy of photobiostimulation, which was also used in a pilot test of clinical application.